2000
DOI: 10.1007/s101520050012
|View full text |Cite
|
Sign up to set email alerts
|

Material exchange and food web of seagrass beds in the Sylt-Rømø Bight: how significant are community changes at the ecosystem level?

Abstract: Material exchange, biodiversity and trophic transfer within the food web were investigated in two different types of intertidal seagrass beds: a sheltered, dense Zostera marina bed and a more exposed, sparse Z. noltii bed, in the Northern Wadden Sea. Both types of Zostera beds show a seasonal development of aboveground biomass, and therefore measurements were carried out during the vegetation period in summer. The exchange of particles and nutrients between seagrass beds and the overlying water was measured di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 112 publications
0
33
0
Order By: Relevance
“…For example, Gätje & Reise (1998) provided detailed information and summaries of ecological data on virtually the entire ecological spectrum from nutrient fluxes to the abundance of fish and bird communities. The flow of energy in a seagrass community in the Bight has been described by Asmus & Asmus (2000), as well as for the food web of the tidal flats (Asmus & Asmus 1985, Asmus 1994. Sprung et al (2001) reported on energy flow in the benthic assemblages of the intertidal area of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gätje & Reise (1998) provided detailed information and summaries of ecological data on virtually the entire ecological spectrum from nutrient fluxes to the abundance of fish and bird communities. The flow of energy in a seagrass community in the Bight has been described by Asmus & Asmus (2000), as well as for the food web of the tidal flats (Asmus & Asmus 1985, Asmus 1994. Sprung et al (2001) reported on energy flow in the benthic assemblages of the intertidal area of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…nutrient cycling, productivity, can be closely related to species abundance. To give an example, the particle and nutrient sink in two Zostera meadows in Sylt, North Sea, was positively correlated with their density (ASMUS & ASMUS, 2000). A positive relation between shoot density of seagrasses and fish and shrimp density was also documented (FONSECA et al, 1996a, b).…”
Section: Discussionmentioning
confidence: 96%
“…These communities not only form the basis of natural, pristine marine environments (PANAYOTIDIS et al, 2001) but also support many ecosystem services, e.g. sustain biodiversity (DEN HARTOG, 1970;PHILLIPS & MEŇEZ, 1988;NIENHUIS, 1992), maintain fish habitat (HARMELIN-VIVIEN et al, 1995;POLLARD, 1984;BELL et al, 1992;FRANCOUR, 1997;EDGAR, 1999b;BLADER et al, 2000), offer detritus to the trophic chain (EDGAR, 1999a), maintain water quality (BULTHUIS et al, 1984;DAUBY et al, 1995;GACIA et al, 1999;ASMUS & ASMUS, 2000), stabilize sediment and control erosion (FONSECA, 1996;ASMUS & ASMUS, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this bioturbation is a cause of the Zostera decline remains to be seen. High numbers of invertebrates are typically associated with Zostera beds (Heck et al 1995;Asmus and Asmus 2000). Thus the integrity of wildfowl populations that feed on these invertebrates is indirectly associated with the health of the Zostera meadows.…”
Section: Discussionmentioning
confidence: 99%